2003
DOI: 10.1002/ajmg.b.20091
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping using haplotype and model‐free linkage analysis supports previous evidence for a locus predisposing to severe bipolar disorder at 5q31‐33

Abstract: We report further evidence for our previous suggestion [Garner et al., 2001: Am J Hum Genet 68:1061-1064] of a locus on 5q predisposing to bipolar I disorder (BP-I) in an extended Costa Rican pedigree. We genotyped additional microsatellite markers in this region and applied a multi-point non-parametric linkage analysis (SimWalk2). Significant identity-by-descent allele sharing among affected relatives was observed for all of the 20 markers tested in a segment of approximately 15 cM. Most affected individuals … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 14 publications
(20 reference statements)
0
18
0
Order By: Relevance
“…This locus is associated with BD (Lewis et al, 2003;Hong et al, 2004;Herzberg et al, 2006;Kerner et al, 2007). A recent study demonstrated a significant increase in homozygosity of the minor allele, which contains a single-nucleotide polymorphism in a putative enhancer for the Pcdha gene, in patients with BD (Pedrosa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…This locus is associated with BD (Lewis et al, 2003;Hong et al, 2004;Herzberg et al, 2006;Kerner et al, 2007). A recent study demonstrated a significant increase in homozygosity of the minor allele, which contains a single-nucleotide polymorphism in a putative enhancer for the Pcdha gene, in patients with BD (Pedrosa et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Previous findings on chromosome 5q have been reported, but these are more distal to our region: Coon et al [1993] reported a LOD score of 1.4 with the marker D5S62 at 5q35. More recently, Hong et al [2004] reported significant identity-by-descent allele sharing among affected relatives in an extended Costa Rican pedigree in the region 5q31-33. Such regions are, however, 18-56 cM from our finding.…”
Section: Linkage Analyses and Genetic Parametersmentioning
confidence: 98%
“…Consequently, mortalin overexpression is linked to cancer research and has been studied in this respect for many years. Human mortalin (HSPA9) is encoded on a single gene, which has been assigned to chromosome 5-band q31.1 (Xie et al 2000), a gene locus previously implicated with various neurological disorders (Crowe and Vieland 1999;Hong et al 2004;Lewis et al 2003;Sklar et al 2004). Similar reports have now implicated mortalin as a key protein in Parkinson's disease, specifically demonstrating that mortalin is significantly reduced in the early onset of the disease and worsens during the progression of the disease (Shi et al 2008).…”
Section: Discussionmentioning
confidence: 99%